ProNGF Drives Localized and Cell Selective Parvalbumin Interneuron and Perineuronal Net Depletion in the Dentate Gyrus of Transgenic Mice - Fasulo, Luisa; Brandi, Rossella; Arisi, Ivan; La Regina, Federico; Berretta, Nicola; Capsoni, Simona; D'Onofrio, Mara; Cattaneo, Antonino (Frontiers in Molecular Neuroscience, 2017)
ProNGF, the precursor of mature Nerve Growth Factor (NGF), is the most abundant NGF form in the brain and increases markedly in the cortex in Alzheimer’s Disease (AD), relative to mature NGF. A large body of evidence shows that the actions of ProNGF and mature NGF are often conflicting, depending on the receptors expressed in target cells. TgproNGF#3 mice, expressing furin-cleavage resistant proNGF in CNS neurons, directly reveal consequences of increased proNGF levels on brain homeostasis. Their phenotype clearly indicates that proNGF can be a driver of neurodegeneration, including severe learning and memory behavioural deficits, cholinergic deficits and diffuse immunoreactivity for A-beta and A-beta-oligomers. In aged TgproNGF#3 mice spontaneous epileptic-like events are detected in entorhinal cortex-hippocampal slices, suggesting occurrence of excitatory(E) imbalance. In this paper we investigate the molecular events linking increased proNGF levels to the epileptiform activity detected in hippocampal slices. The occurrence of spontaneous epileptiform discharges in the hippocampal network in TgproNGF#3 mice suggests an impaired inhibitory interneuron homeostasis. In the present study, we detect the onset of hippocampal epileptiform events at 1-month of age. Later, we observe a regional- and cellular-selective Parvalbumin interneuron and perineuronal net (PNN) depletion in the dentate gyrus (DG), but not in other hippocampal regions of TgproNGF#3 mice. These results demonstrate that, in the hippocampus, the DG is selectively vulnerable to altered proNGF/NGF signalling. Parvalbumin interneuron depletion is also observed in the amygdala, a region strongly connected to the hippocampus and likewise receiving cholinergic afferences. Transcriptome analysis of TgproNGF#3 hippocampus reveals a proNGF signature with broad down-regulation of transcription. The most affected mRNAs modulated at early times belong to synaptic transmission and plasticity and extracellular matrix gene families. Moreover, alterations in the expression of selected BDNF splice variants were observed. Our results provide further mechanistic insights into the vicious negative cycle linking proNGF and neurodegeneration, confirming the regulation of Ehomeostasis as a crucial mediating mechanism.